2015
DOI: 10.1016/j.omsc.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Nasopalatine duct cyst associated with dental implant treatment: A case report

Abstract: A B S T R A C TMaxillary anterior implants are associated with the risk of nasopalatine canal damage. Here we present the case of a 37-year-old man who developed a nasopalatine duct cyst after maxillary implant placement. The patient received an implant 3 months after the extraction of a fractured maxillary right central incisor. At a maintenance visit 9 years after the procedure, he complained of swelling and mild pain in the palatal region of the implant. A panoramic radiograph and computed tomography (CT) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There have been reported cases in literature of nasopalatine canal cyst associated with dental implants. The published data have emphasized on preoperative 3D planning using cone beam computed tomography18,19 prior to implant placement procedures to avoid complications. Sukhegawa et al have suggested that trauma to the nasopalatine canal during the surgical procedure of implant placement can lead to cyst 18 development.…”
mentioning
confidence: 99%
“…There have been reported cases in literature of nasopalatine canal cyst associated with dental implants. The published data have emphasized on preoperative 3D planning using cone beam computed tomography18,19 prior to implant placement procedures to avoid complications. Sukhegawa et al have suggested that trauma to the nasopalatine canal during the surgical procedure of implant placement can lead to cyst 18 development.…”
mentioning
confidence: 99%
“…As Table 1 shows, there is still no consensus on the classification of IPL. The included reports (70 patients/76 implants) were preliminarily distributed in Penarrocha-Diago et al ’s classification [ 5 ]: 31 implants were inactive [ 8 , 12 , 13 , 17 , 18 , 20 , 21 , 26 , 27 , 29 , 30 , 33 , 36 ], and 46 implants were active, with acute non-suppurated(1) [ 13 ], acute suppurated (10) [ 6 , 7 , 14 , 16 , 19 , 25 , 28 , 31 , 32 ], subacute/suppurated-fistulized(7) [ 15 , 22 – 24 , 33 , 34 ], unclear stage(26) [ 35 ]. It should be noted that histopathological findings in some cases did not match Penarrocha-Diago et al’s classification to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that histopathological findings in some cases did not match Penarrocha-Diago et al’s classification to some extent. For example, Nedir et al’s [ 22 ] case presented clinical characteristics similar to the subacute/suppurated-fistulized phase, however, the detected foreign body was considered to be the culprit rather than residual infection; Cases presenting only localized pain and radiography were defined as acute suppurating [ 6 , 7 , 31 ], whereas histopathological evidence showed implant periapical cyst rather than inflammation; Asymptomatic cases were directly classified as inactive lesions according to the previous criteria, which led to the inclusion of cystic entity. However, the interpretation of the inactive item did not comprise cyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic planning foresaw different approaches: implant and cyst removal, cystectomy, and the resection of the apical portion of the implant inside the cyst cavity [10,21]. Sukegawa et al decided to perform a cystectomy, but did not perform any implant extractions due to implant stability and no report of perimplant bone resorption [22].…”
Section: Discussionmentioning
confidence: 99%